MAGNETIC RESONANCE IMAGING (MRI) FOR PELVIC ORGAN PROLAPSE - M. N. Barinova; A. E. Solopova; N. V. Tupikina; G. R. Kasyan; D. Ju. Pushkar (Акушерство, гинекология и репродукция, 2016)
The purpose of our study was to improve th e quality of pelvic organ prolapse (POP) diagnostic using static and dynamic MRI. We com pared 60 MRI in woman with POP and 20 controls according to the grade of prolapses and pelvic floor relaxation, asymmetry of pubococcygeal and puborectalis muscle. According to the prevalent component of theprolapsus, the patien ts divided: сystocele – 21 (35%), сystourethrocele – 9 (15%), urethrocele – 3 (5%), vaginal prolapse – 6 (10%), uterine prolapse – 6 (10%), enterocele – 3 (5%), rectocele – 12 (20%). Measurements of the supporting structures were significant (p<.05) in the identification of pelvic floor laxity. The combined static and dynamic MRI canprovide useful information according certain structural abnormalities with specific disfunction, and could be necessary for surgeons as a complement method in planning operation technique.